Design and Dynamic Modification of Multi-condition Shift Schedule for Automotive Automatic Transmission - Ma Wenjie; Zhang Xiaocong; Yan Zhengjun; Chen Wenjun; Wang Weida (Jixie chuandong)
Combined dynamic shift schedule for the hydraulic automatic transmission is designed.The fuzzy control with the vehicle speed,throttle opening and acceleration as the control parameters are used to modify the shift schedule based on the dynamic characteristics of engine.The ramp conditions are amended by the speed attenuated dynamic shift schedule.The simulation results show that dynamic revised shift schedule has a better power performance and is more in line with driver intention.The amended shift schedules under ramp conditions can solve the problems of shift cycle under uphill condition and rising to higher shift under downhill condition,so that frequent shifting is avoided.